2018
DOI: 10.3390/s18020614
|View full text |Cite
|
Sign up to set email alerts
|

Feature-Level Fusion of Surface Electromyography for Activity Monitoring

Abstract: Surface electromyography (sEMG) signals are commonly used in activity monitoring and rehabilitation applications as they reflect effectively the motor intentions of users. However, real-time sEMG signals are non-stationary and vary to a large extent within the time frame of signals. Although previous studies have focused on the issues, their results have not been satisfactory. Therefore, we present a new method of conducting feature-level fusion to obtain a new feature space for sEMG signals. Eight activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The development of EMG feature extraction and classification methods that are robust to noise is also important [64,65], as is the reduction of data (or dimensionality) when dealing with large-scale data sets. Determining relevant and meaningful features from a given larger set of features which may contain irrelevant, redundant, or noisy information is commonly accomplished using either feature selection [66][67][68][69] or feature projection methods [70][71][72][73]. When properly executed, these methods not only reduce the impact of noise and irrelevant information, but also the amount of computational time required for classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of EMG feature extraction and classification methods that are robust to noise is also important [64,65], as is the reduction of data (or dimensionality) when dealing with large-scale data sets. Determining relevant and meaningful features from a given larger set of features which may contain irrelevant, redundant, or noisy information is commonly accomplished using either feature selection [66][67][68][69] or feature projection methods [70][71][72][73]. When properly executed, these methods not only reduce the impact of noise and irrelevant information, but also the amount of computational time required for classification.…”
Section: Discussionmentioning
confidence: 99%
“…For feature selection, some potential and well-known population-based metaheuristic methods, such as genetic algorithm (GA), particle swarm optimization (PSO), and ant colony optimization (ACO), have been found to be effective in selecting an optimal EMG feature set (e.g., [67][68][69]). These feature selection methods have been developed to work in parallel computing as well as on graphics processing units (GPU) [87,88].…”
Section: Feature Engineeringmentioning
confidence: 99%
“…Kim et al [70] identified synergies using iterative K-mean clustering and intraclass correlation. Hierarchical, model-based, fuzzy c means clustering has been employed to group gait patterns [69,[71][72][73]. Dolatabadi et al [71] used mixture model clustering on spatiotemporal gait pattern to classify pathological gait.…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…Pathological disorders such as cerebral palsy that show higher inter-stride variability can be analyzed with a hierarchical clustering method proposed by Rosati et al [72]. Feature Fusion technique with Davies Bouldin Index (DBI) based on fuzzy C means algorithm was used in a trip/fall study [73]. The DBI can be used to evaluate the clustering algorithm.…”
Section: Unsupervised Learningmentioning
confidence: 99%
See 1 more Smart Citation